Supressão do nematoide Pratylenchus brachyurus e estímulo ao crescimento da soja por fungo micorrízico arbuscular - Trentin, Edicarla (2016)
The production expansion areas of soybean monoculture system result in increased fertilizers and pesticides application, and the intensification of some phytosanitary problems such as the damage caused by plant-parasitic nematodes. The arbuscular mycorrhizal fungi (AMF) increase plant growth and reduce the problems caused by nematodes in soybean. The objective of this work was to study the effect of arbuscular mycorrhizal fungi Rhizophagus clarus in the growth of soybean plants and the nematode Pratylenchus brachyurus suppression. Two trials were conducted in a greenhouse. In the first experiment evaluated the growth of soybeans in the presence and absence of the mycorrhizal fungus R. clarus. In the second trial was carry out the damage caused by the P. brachyurus in soybean grown in the presence and absence of R. clarus. In soybean flowering period evaluated the height, stem diameter, the dry matter of root and shoot, nodulation, the relative chlorophyll index, the nutrient content of the plant tissue, the number of the nematode in soil and penetrated to the root system, the reproduction factor of the nematode, the number of fungal spores in the soil and mycorrhizal colonization of roots. The results showed that mycorrhiza increased the growth, nodulation and nutrient uptake of soybean plants grown in soil with or without nematode. The mycorrhizal colonization reduced the penetration of the nematode in soybean roots, despite the greater number of nematodes in the soil. The presence of the nematode influenced mycorrhizal colonization of soybean plants. The use of sustainable management practices that favor the populations of AMF in the soil, can be a strategy for increasing and/or maintaining crop yields and reducing the affect caused by the P. brachyurus.